2017
DOI: 10.1016/j.biocontrol.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning the entomopathogenic nematodes Steinernema carpocapsae and Heterorhabditis megidis by pre-application storage improves efficacy against black vine weevil, Otiorhynchus sulcatus (Coleoptera: Curculionidae) at low and moderate temperatures

Abstract: h i g h l i g h t s Efficacy of H. megidis and S. carpocapsae is improved by storage at 9°C for 3-6 weeks. Efficacy is improved across a range of test conditions, both above and below 9°C. 9°C-stored H. megidis kill more vine weevil larvae than S. kraussei in winter. 9°C storage of H. megidis compensates for lower application rate against vine weevil. Success of S. kraussei is strongly influenced by vine weevil instar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For H. megidis , conditions similar to those used in the present study have been shown to profoundly influence infectivity (a compound trait of movement towards and entry into insects), which increased with time, especially in IJs maintained at 9°C (Griffin, 1996 ; Fitters et al ., 2001 ). Similar effects have been documented for steinernematids (Koppenhöfer et al ., 2013 ; Guy et al ., 2017 ; Yadav and Eleftherianos, 2018 ). Host-finding and infection in soil involve a series of steps, including dispersal, host-finding and host-recognition and acceptance (Lewis et al ., 1995 a ; Griffin, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For H. megidis , conditions similar to those used in the present study have been shown to profoundly influence infectivity (a compound trait of movement towards and entry into insects), which increased with time, especially in IJs maintained at 9°C (Griffin, 1996 ; Fitters et al ., 2001 ). Similar effects have been documented for steinernematids (Koppenhöfer et al ., 2013 ; Guy et al ., 2017 ; Yadav and Eleftherianos, 2018 ). Host-finding and infection in soil involve a series of steps, including dispersal, host-finding and host-recognition and acceptance (Lewis et al ., 1995 a ; Griffin, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to investigate the effects of temperature and time on the behaviour, stress tolerance and proteome of Steinernema carpocapsae , the best studied and most economically important EPN species. We also include Heterorhabditis megidis in the behavioural assays; the behaviour of this species has been extensively studied with respect to storage temperature and time (Griffin, 1996 ; O'Leary et al ., 1998 ; Fitters and Griffin, 2004 ; Guy et al ., 2017 ). We have recently shown, using quantitative label-free proteomics, that the proteomes of S. carpocapsae and H. megidis IJs differ in their response to temperature: when newly emerged IJs were transferred from a culture temperature of 20 to 9°C, the proteome of S. carpocapsae underwent profound changes that were maintained during further storage at that temperature, while the proteome of H. megidis underwent more gradual changes over time at both 20 and 9°C (Lillis et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another work reported that Heterorhabditis bacteriophora (strain Oswego) is able to inhibit the development of late Sitona hispidulus instars [ 88 ]. The efficacy of EPNs is often restricted by environmental conditions [ 89 ]. When temperature and soil type are optimal, EPN application in the field can be a successful measure against soil-dwelling larvae [ 90 ].…”
Section: Integrated Pest Managementmentioning
confidence: 99%
“…Temperature can also be used as a tool to improve BCA efficacy as in entomopathogenic nematodes (EPNs) (Baiocchi et al 2017) which could control PPNs (Jagdale et al 2009; Abd-Elgawad 2017b). For instance, conditioning Steinernema carpocapsae and Heterorhabditis megidis for 3 weeks at 9°C enhanced their biocontrol efficacy (Guy et al 2017). Other abiotic and biotic interactions are worthy of interest for BCA predation or competition.…”
Section: Environmental and Biological Factorsmentioning
confidence: 99%